THE RELATIONSHIP BETWEEN AGE AND DURATION OF SURGERY WITH THE INCIDENCE OF POST ANESTHESIA SHIVERING IN SECTION CAESAREAN PATIENTS AT BENDAN HOSPITAL PEKALONGAN CITY - Triyadi, Ficky; Mixrova Sebayang, Septian; Burhan, Asmat; Dwi Agus Yulianto; Refa Teja Muti (Java Nursing Journal, 2024)
Background: Shivering is a physiological response to exposure to cold and the body's next steps to maintain heat after peripheral vasoconstriction. The incidence of shivering is caused by several factors including age and length of surgery. Postanesthesia shivering is involuntary oscillatory muscle activity during early recovery after anesthesia. Objective: This study aims to determine the relationship between age and duration of surgery with the incidence of shivering after anesthesia in caesarean section patients at Bendan Hospital, Pekalongan City. Methods: This research includes quantitative research with the type of analytical correlational observational research with a cross sectional approach. The subjects or samples used were 50 caesarean section patients. Determination of subjects was carried out using consecutive sampling technique. Data collection was carried out using an observation sheet for the degree of shivering. Result: Based on the research, the results of the Spearman rank test were obtained with a value of (p) 0.0004 < 0.05 between age and the incidence of shivering and p 0.000 < 0.05 between the length of operation and the incidence of shivering. Conclusion: The conclusion of this study is that there is a relationship between age and length of operation and the incidence of post-anesthesia shivering in caesarean section patients.